Prophylactic Drain Placement in Childhood Perforated Appendicitis: Does Spillage Matter? - Schmidt, Yannick Michael; Wendling-Keim, Danielle; von Schweinitz, Dietrich; Hubertus, Jochen; Berger, Michael (Frontiers in Pediatrics, 2020)
Background: Prophylactic abdominal drains for perforated appendicitis in children have generally been regarded as obsolete because several studies showed inferior results for drain placement in the past. Despite these results, prophylactic abdominal drains for perforated appendicitis remain omnipresent in pediatric surgery especially when gross spillage is observed at the time of appendectomy. Here, we hypothesize that even if accounting for gross intra-abdominal spillage, prophylactic drain placement for perforated appendicitis in children are not beneficial. Patients and Methods: The charts of all children (< 18 years) who underwent appendectomy at our institution from July 2013 to March 2020 were analyzed. The data from 65 patients who presented with perforated appendicitis were included. Patients were grouped according to the amount of intraoperative spillage. Demographics, laboratory data, operative findings, and postoperative outcomes were analyzed. Results: Of all patients, 34 were male and 31 were female with a mean age of 10.5 +/-3.7 years. There were no statistically significant differences between the groups for age and gender (p=0.6985, and p=0.6222, respectively). Prophylactic drains were placed according to the surgeon’s preference in 32 children. There were no statistically significant differences between the groups in the rate of intra-abdominal abscess formation, wound infection, and bowel obstruction, regardless of the amount of spillage encountered during appendectomy. However, independently of the amount of spillage, the length of hospital stay (LOH) was longer in the children in which a drain had been placed (p=0.0041). Conclusion: In our cohort, we could not find a benefit from drain placement even in case of gross spillage at the time of appendectomy. Rather, drain placement was associated with an increase in LOH.